Route-Truck Performance Evaluation of High Capacity Transportation Truck and Traditional Smaller Truck - Hassan, Tajudeen Ola (My University, 2019)
High capacity truck and traditional truck present opportunities and challenges for logistics providers. This paper examines cost and revenue as the two main evaluation criteria of optimum truck selection decision between high capacity trucks and traditional trucks; also design a model that present the processes involved in route-truck performance evaluation for the case company, a transport logistics service company with specialty in food and dairy products delivery. One-year route-truck related data from different sources was examined to compare cost and revenue performances on three different routes. Elements such as cost per pallet and profit per pallet were considered the best metrics for route-truck comparison, because, they spread total truck operating cost and revenue on a unit pallet delivered to customers on all routes. Research findings from overall performance assessment indicate, high capacity trucks (HCT) generate more revenue and profits (1% and 5.6% ) respectively, when the utilization rate of its capacity advantage is at maximum, but has a higher cost per kilometre, 9.9% more than traditional truck; traditional trucks have lower intra-route performance operating costs and profits, due to lower fuel consumption rate and smaller capacities. However, other factors such as routes distances, weather changes (seasonal), nature and size of truck engine, and drivers’ performances are important in determining optimum truck for logistics service providers. Efficient vehicle routing and scheduling will lead to effective use of company assets that would result in improve profitability and customer satisfaction for the company.
Keywords: High Capacity Truck, Traditional Truck, Performance Evaluation, Cost, Revenue, Profit; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management